Identification of genomic instability related lncRNA signature with prognostic value and its role in cancer immunotherapy in pancreatic cancer - Zhu, Xiaole; Yu, Rong; Peng, Yunpeng; Miao, Yi; Jiang, Kuirong; Li, Qiang (Frontiers in Genetics, 2022)
Abstract: Background: Increasing evidence suggested the critical roles for lncRNAs in the maintenance of genomic stability. However, the identification of genomic instability related lncRNA signature (GILncSig) and its role in pancreatic cancer remain largely unexplored. Methods: In the present study, a systematic analysis of lncRNA expression profiles and somatic mutation profiles was performed in pancreatic cancer patients from TCGA. We then development a risk score model to describe the characteristics of the model and verify its prediction accuracy. ESTIMATE algorithm, single-sample gene set enrichment analysis (ssGSEA), and CIBERSORT analysis were employed to reveal the correlation between tumor immune microenvironment, immune infiltration ,immune checkpoint blockade (ICB) therapy and GILncSig in pancreatic cancer. Results: We identified 206 GILncSig, of which five were screened to develop a prognostic GInLncSig model. Multivariate Cox regression analysis and stratified analysis revealed that the prognostic value of the GILncSig was independent of other clinical variables. ROC analysis suggested that GILncSig is better than the existing lncRNA-related signatures in predicting survival. Additionally, the prognostic performance of the GILncSig was also found to be favorable in patients carrying wild-type KRAS, TP53 and SMAD4. Besides, a nomogram exhibited appreciable reliability for clinical application in predicting the prognosis of patients. Finally, the relationship between GInLncSig model and immune landscape in pancreatic cancer reflected its application value in clinical immunotherapy. Conclusion: In summary, the GILncSig identified by us may serve as novel prognostic biomarkers, and could have crucial role in immunotherapy decisions for pancreatic cancer patients.